PENGARUH SERVICE QUALITY, CUSTOMER VALUE, CITRA PERUSAHAAN DAN SWITCHING COST TERHADAP LOYALITAS KONSUMEN DENGAN EXPERIENTIAL MARKETING SEBAGAI VARIABEL INTERVENING PADA PT ASURANSI JASINDO KANTOR CABANG JEMBER - Angkat Samekto; Imam Suroso; Dessy Wulandari (STIE Mandala Jember, 2016)
The aim of this study was to examine the effect on service quality, customer value,corporate image on experiential marketing PT Asuransi Jasa Indonesia; to examine theinfluence of service quality, customer value, corporate image, switching cost oncustomer loyalty PT Asuransi Jasa Indonesia and to examine the effect of experientialmarketing on customer loyalty PT Asuransi Jasa Indonesia. The object under study is acustomer of PT Asuransi Jasa Indonesia. This study was to describe the facts and to testthe hypothesis to see relationships between variables, The design of this research studyexplanation (explanatory research / confirmatory research). Sampling technique usedin this study was purposive sampling. The population in this study is limited to the retailconsumer segment is the insurance services PT.Asuransi Jasindo Jember fire insurancepolicy holders, vehicle insurance and miscellaneous insurance in 2013 , amounting to986 people.